Musik dalam Perkembangan Potensi Akademik Siswa Sekolah Dasar - Meiske Maythy Lasut, Elizabeth; Kainde, Sandra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2025)
Education is determining the result of the human being. Education also gives a huge contribution regarding the improvement of a nation. The effort to increase the quality process and the students’ learning outcome from primary level need to be realized in order to obtain the quality of human resource which is will be able to support the national advancement. The work should be the teachers’ and parents’ duty and responsible. Teachers’ role is very important to improve students’ ability through teaching and learning process at school directly. Teachers need to find out a helpful method in elaborating students’ way of think in order to learn easily to achieve the goals. There are several methods and facilitations which are used to push students’ learning potency. Music is one of various methods that used to help the teaching and learning process. Learning music is assumed as one of the triggers of students to learn better. This literature review is conducted to know how far the role of music in developing elementary students’ academic potential.